The heartbeat of the youth development field : professional journeys of growth, connection, and transformation - Hall, Georgia; Gallagher, Jan; Starr, Elizabeth (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"Youth work is a sacred opportunity to make a significant difference in the lives of children and youth. Through a seamless thread of research and personal essay narrative this volume, The Heartbeat of the Youth Development Field: Professional Journeys of Growth, Connection, and Transformation shines a light on the intricate connections between research and practice touching upon both the vulnerability and triumph of work. The voices of youth workers in this volume, that we hear so passionately, lead to the inescapable conclusion that programs and policies for youth must be informed by these same voices and the values they express. Other out-of-school time (OST) and youth development workers will see their own stories reflected in the practitioner essays. The research chapters and essays alike are valuable resources to faculty leaders of university OST and youth work graduate and certificate programs, as well as to program leaders and others who conduct professional development for OST staff. The lived stories of OST practitioners and the youth they serve and inspire can be - should be - important drivers of research and policy. The book is organized in five sections, each rooted in a research chapter. The middle three sections add five essays, written by OST practitioners and reflect the theoretical and experiential issues of the research chapters. Each of the essay sections ends with notes and reflection questions that can guide individual readers or serve as discussion starters for staff professional development or communities of practice. We hope this book shows OST workers, researchers, funders, and policymakers, as well as other education professionals, how youth workers' lived experiences inspire their ability to build the relationships that are the foundation of positive and healthy youth development. From relationships comes engagement, and from engagement, transformation-centered in equity, inclusion, and belonging. No one is better able to advocate for these truths than the professionals who found themselves-by whatever means-working with young people to bring positive change to their lives, their communities, and our world"-- Provided by publisher.
Keywords: Youth development.; Social work with youth.; Education -- Counseling -- General.; Counselling and care of students.; elektronické knihy; electronic books